140k views
2 votes
F(x) = -2x
g(x) = -2x
ƒ(g(x)) =
g(f(x)) =

User Sjy
by
5.5k points

1 Answer

2 votes
Ok so when combining functions like these, you need to that the value inside your parentheses is the new x that you replace in the corresponding function.

For example f(g(x)) would technically be f(-2x) where you would replace all of your x values in f(x) to get f(g(x))= -2(-2x) which is equal to 4x when simplified.

Luckily, since both of your functions are the same thing, this means that g(f(x)) is also 4x.

Hope that helps!
User Jabal Logian
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.